Digital Vigilantism or Self-Branding? A Psychological and Managerial Analysis of Stalker-Shaming Content on TikTok - Purnamaningtyas Kusuma Dewi; Muhammad Faaiz Pandu Dewanata; Su’ad Jauharoh (Sean Institute, 2026)
The rise of TikTok as a short-video platform has given rise to a distinctive digital phenomenon: stalker-shaming content, in which predominantly female creators publicly expose and humiliate individuals who monitor their social media accounts, typically ex-romantic partners. Despite its growing prevalence, this behavior remains theoretically underexplored, situated at the intersection of digital psychology and management science. This study aims to analyze stalker-shaming content on TikTok as a simultaneous act of relational aggression and strategic self-branding, and to identify the role of algorithmic amplification in sustaining this behavior. Employing a Bibliometric-Systematic Literature Review (B-SLR) approach, this study synthesized 24 articles retrieved through Scopus keyword search and manual snowballing, analyzed using VOSviewer and the PRISMA 2020 framework. Bibliometric mapping revealed three converging research gaps: a platform gap centered on Facebook rather than TikTok, a construct gap marked by the complete absence of impression management and personal branding keywords, and a temporal gap with the existing corpus concentrated in 2014–2015. Thematic synthesis yielded a four-layer conceptual model integrating Impression Management Theory [1], Self-Enhancement Theory, the Relational Aggression Framework [2], and Personal Branding Theory [3], moderated by TikTok's algorithmic architecture. Findings suggest that stalker-shaming functions simultaneously as maladaptive psychological coping and reactive personal branding, structurally incentivized by platform reward systems. This study contributes an original interdisciplinary framework with implications for digital wellbeing practice and personal brand management in algorithmically mediated environments.